Quranic analysis: a critical examination of gender in Islamic and western paradigms - Zubairi, Furhan Majtaba; Badi, Jamal Ahmed Bashier; Ruhullah, Mohammad Eisa (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The modern era epitomizes a period of profound transformation across diverse spheres including science, technology, politics, and warfare, characterized by discovery, innovation, and globalization. European powers and their colonies spearheaded a comprehensive colonization endeavor encompassing politics, economics, and culture, shaping what we recognize today as the modern world. This era heralded the ascendance of capitalism, liberalism, materialism, and globalization, predominantly led by Western hegemony, notably post-Cold War American capital, extending its influence globally. Modernity, with its core tenets of moral autonomy, human rights, civil equality, consumerism, market freedom, and secularism, presents a formidable challenge to traditional religious frameworks, particularly within the Abrahamic Faiths. The secularization of society,